2019
DOI: 10.1021/acsomega.8b02275
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Antioxidants and Fatty Acid Degradation Using a Combination Approach of GC-FID and Square-Wave Voltammetry

Abstract: Analytical methodology for direct investigation of antioxidant systems continues to be a pressing research area. Consumer demand for natural products requires an increase in natural antioxidants; thus, fast, high-throughput, and cost-effective screening methods are in demand. In this study, square-wave voltammetry and gas chromatography with flame ionization detection (GC-FID) were used in conjunction to monitor antioxidant and fatty acid degradation, respectively, during the accelerated degradation of an omeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…One of the most widely studied properties of sesamol is its antioxidant activity. It has been proved to have effective capacity for inhibiting hydroxyl radical-induced deoxyribose degradation and lipid peroxidation , which helps protecting plasma, low-density lipoprotein, and erythrocyte membrane from oxidation. Sesamol also induces nitric oxide (the most important vascular relaxing factor) release from endothelial cells. , It has scavenging effects against hydroxyl (OH • ), superoxide anion (O 2 •– ), nitric oxide, hydrogen peroxide (H 2 O 2 ), and other oxidants, in some cases with an efficiency higher, or equal to those of ascorbic acid and vitamin E . Based on its free radical scavenging activity, it has been suggested to use sesamol in the management of Huntington’s, Alzheimer’s, and Parkinson’s diseases, auto-immunity disorders, and brain damage in autism. …”
Section: Introductionmentioning
confidence: 99%
“…One of the most widely studied properties of sesamol is its antioxidant activity. It has been proved to have effective capacity for inhibiting hydroxyl radical-induced deoxyribose degradation and lipid peroxidation , which helps protecting plasma, low-density lipoprotein, and erythrocyte membrane from oxidation. Sesamol also induces nitric oxide (the most important vascular relaxing factor) release from endothelial cells. , It has scavenging effects against hydroxyl (OH • ), superoxide anion (O 2 •– ), nitric oxide, hydrogen peroxide (H 2 O 2 ), and other oxidants, in some cases with an efficiency higher, or equal to those of ascorbic acid and vitamin E . Based on its free radical scavenging activity, it has been suggested to use sesamol in the management of Huntington’s, Alzheimer’s, and Parkinson’s diseases, auto-immunity disorders, and brain damage in autism. …”
Section: Introductionmentioning
confidence: 99%
“…38 These compounds show a symbiotic behavior, modulating lipid degradation, thanks to the antioxidant capacity of carotenoids, while maintaining greater stability and bioactivity in compounds such as astaxanthin when in esterified form. 39 This is a clear advantage of using microalga in a paste form (as a whole), as opposed to isolating a single compound by extraction.…”
Section: Papermentioning
confidence: 99%
“…Studies have shown phospholipids have emulsifying properties that improve bioavailability of EPA and DHA in krill oil (Rundblad et al, 2018; Seto et al, 2018). During storage, omega‐3 fatty acids in fish oil may generate oxidation products that may negative impact overall health (Keene et al, 2019; Song et al, 2020); of note, astaxanthin exerts powerful antioxidant property, which suppresses oxidation of omega‐3 fatty acids in krill oil (Ulven and Holven, 2015).…”
Section: Introductionmentioning
confidence: 99%